Manajemen Pembinaan Anak di Lembaga Pembinaan Khusus Anak Klas II Jakarta dalam Rangka Perlindungan Hak Anak Pidana - Eka Rista Harimurti (Jurnal Ilmiah Wahana Pendidikan, 2019)
The purpose of this study was to learn how to manage child development in the Special Class Guidance Institution for Children (LPKA) Class II Jakarta in order to protect the rights of children involved through management of planning, organizing and monitoring management. The researcher used qualitative with the case study method. The study was conducted in Class II LPKA Jakarta under the auspices of the Salemba Class II A Lapas located at the address of Jl. Percetakan Negara Number 88 A, RT 12 RW 4, Rawasari, Cempaka Putih. Central Jakarta City. Educating LPKA Class II A Jakarta has been running optimally, with the realization of the flagship programs of the Directorate General of Corrections by Lapas Class II Salemba which oversees LPKA Class II A Jakarta, specifically for coaching looking for special training programs for LPKA Students. Jakarta Class II LPKA which is under the auspices of Class II of the Salemba Lapas has been transferred to LPKA Students who provide protection for children's rights.